Efektivitas Permainan Tradisional Ucing Bal Terhadap Perkembangan Sosial di Taman Kanak-Kanak Pertiwi 3 Padang - Febriyanti, Ulfa; Saridewi, Saridewi (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2019)
Abstract This research was to determine the sosial develompment of children from 5 to 6 aged using Ucing bal games at kindergarten Pertiwi 3 in Padang. This research begins with the assumption that the ucing bal game can stimulate the child’s social development. Many children are still individual and do not want to cooperate with friends, also children prefer to do their own activities. This research used quantitative research with experimental methods in the form of quashi experimental. The population of this research was Pertiwi 3 in Padang, class B2 as an experimental class while B4 as a control class. Each sample consist of 12 children. The research was usiang cluster sampling technic and this research was using action research and documentation to collect the data. The average social ability of early childhood in the experimental class was 8.30 and the control class was 7.90, while the result of the effect size with Cohen's is 0.98> 0.80. These results concluded that the game ucing bal effective for developing social early childhood 5-6 year.